Cardiac function and quality of life improvement with fasudil hydrochloride in patients with diabetes post-PCI: a randomized controlled trial - Xuejia Yang; Qian Li; Yaning Liu; Ran Chen; Yanjing Liu; Chenghui Sun; Licha Kong; Qiuli Dong (Journal of International Medical Research)
Objective We assessed the efficacy of fasudil hydrochloride, a Rho-kinase inhibitor, as adjunct therapy for enhancing cardiac function, managing blood sugar, and improving quality of life in patients with diabetes who have coronary heart disease (CHD) and who underwent percutaneous coronary intervention (PCI). Methods We conducted a randomized controlled trial including 100 patients with diabetes and CHD who underwent PCI. Participants were randomly assigned to an experimental group receiving fasudil hydrochloride plus standard therapy or a control group receiving standard therapy alone. Treatment outcomes were evaluated over 3 months, focusing on cardiac function, blood sugar levels, and quality of life across physical, social, activities of daily living, and psychological domains. Results The experimental group showed significant improvement in cardiac function and blood sugar control, compared with the control group. Additionally, quality of life scores were markedly higher for the experimental group in all evaluated domains. Conclusions Fasudil hydrochloride effectively targets endothelial dysfunction and atherosclerosis, contributing to better cardiac performance and metabolic regulation. These effects translate into improved post-PCI quality of life for patients with diabetes and CHD. As an adjunct to standard PCI therapy, fasudil hydrochloride treatment offers a promising strategy for enhancing clinical outcomes in this high-risk patient population.